Conservation tillage and residue management improve soil health and crop productivity—Evidence from a rice-maize cropping system in Bangladesh - Sarker, Mamunur Rashid; Galdos, Marcelo Valadares; Challinor, Andrew J.; Huda, Muhammad Shamsul; Chaki, Apurbo K.; Hossain, Akbar (Frontiers in Environmental Science, 2022)
The rice-maize (R-M) system is rapidly expanding in Bangladesh due to its greater suitability for diverse soil types and environments. The present conventional method of cultivating puddled transplanted rice and maize is input-intensive, decreases soil health through intense ploughing, and ultimately reduces farm profitability. There is a need to investigate alternatives. Accordingly, we conducted a replicated two-year (2020–2021) field study to investigate the effects of conservation agriculture (CA) based tillage and crop establishment (TCE) techniques and residue management practices on the physical, chemical, and biological properties of soil along with crop productivity and the profitability of rice-maize systems in the sandy loam soil of Northwest Bangladesh. Two TCE techniques transplanted puddled rice (TPR) followed by conventionally tilled maize (CTM) and strip tillage direct-seeded rice (STDSR) followed by strip-tilled maize (STM) were assigned to the main plots and different percentages of crop residue retention (0, 25, and 50 % by height) were allocated to the subplots. Results showed that a reduction in bulk density (BD), soil penetration resistance (SPR), and increased soil porosity were associated with STDSR /STM-based scenarios (strip tillage coupled with 25 and 50% residue retention). The SOC fractions, such as dissolved organic C (DOC), light and heavy particulate organic matter C (POM-C), MAOM, and microbial biomass C (MBC) levels in the 0–10 cm layer under ST based treatments were 95%, 8%, 6%, 2% and 45% greater, respectively, compared to CT with no residue treatment. When compared to the CT treatment, the DOC, light POM-C, heavy POM-C, and MAOM in the 10–20 cm layer with ST treatment were 8%, 34 %, 25%, 4%, and 37% higher, respectively. ST with residue retention increased average rice, maize, and system yields by 9.2%, 14.0%, and 14.12%, respectively, when compared to CT. The system gross margin and benefit-cost ratio (BCR) were $1515 ha−1 and 1.90 under conventional tillage to $1696 ha−1 and 2.15 under strip-tillage practices. Thus, our study suggests that CA could be an appropriate practice for sustaining soil fertility and crop yield under R-M systems in light-textured soils or other similar soils in Bangladesh.